Animal models of compulsion alcohol drinking: Why we love quinine-resistant intake and what we learned from it - De Oliveira Sergio, Thatiane; Frasier, Raizel M.; Hopf, Frederic W. (Frontiers in Psychiatry, 2023)
Alcohol Use Disorder (AUD) ranks among the most prevalent mental disorders, extracting ~$250 billion/year in the US alone and producing myriad medical and social harms. Also, the number of deaths related to problem drinking has been increasing dramatically. Compulsive alcohol drinking, characterized by intake that persists despite negative consequences, can be particularly important and a major obstacle to treatment. With the number of people suffering from AUD increasing during the past years, there is a critical need to understand the neurobiology related to compulsive drives for alcohol, as well as the development of novel AUD pharmacological therapies. Here we discuss rodent compulsion-like alcohol drinking (CLAD) models, focusing on the two most widely used adverse stimuli to model rodent compulsion-like responding, quinine adulteration of alcohol and footshook-resistant alcohol intake. For both cases, the goal is to uncover behavior patterns and brain circuits that underlie drive for alcohol even in the face of negative consequences. We discuss caveats, benefits, and potential brain mechanisms, of models for consequence-resistant responding for alcohol more generally, and especially highlight some advantages of quinine-resistance over footshook-resistance. Further, since this review contributes to a Special issue focused on Molecular Aspects of Compulsive Drug Use, we discuss our new findings showing how the noradrenergic system is related to CLAD responding. In particular, we comment on the importance of α1 and β adrenergic receptors (ARs) as potential targets for treating AUD.